Study of pressure shock characteristics of pump-controlled hydraulic steering system - Peng, Likun; Qu, Duo; Chen, Jia (Vibroengineering Procedia, 2016)
Owing to the complex working conditions, large load changes and inertia of variable pump, pressure shock seriously lowers the efficiency, stability and accuracy of pump-controlled hydraulic steering system. To study the pressure shock characteristics, a physical model of pump-controlled hydraulic steering system was deduced first, and the system dynamic characteristics were simulated by MATLAB/SIMULINK; then the AMESim model was also established to analyze the shock pressure further. By comparison with the simulation results in SIMULINK, the validity of AMESim model is verified. Based on AMESim model, the influence of the navigation speed, spring stiffness of feedback mechanism and rudder angular velocity to the shock characteristics were analyzed specially. According to the results, the design and control methods to reduce hydraulic shock are obtained, which provide a theoretical basis for improving the characteristics of pump-controlled rudder.